(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The sunflower halva recipe was optimized by replacing sugar and molasses with isomalt and maltitol. A series of experiments were conducted to determine the structural-mechanical indicators of halva samples, confirming the feasibility of using isomalt and maltitol to create an alternative product to the high-calorie halva made according to the classical recipe. Additionally, the technological parameters of its production were justified.